2020
DOI: 10.1093/ecco-jcc/jjz203.790
|View full text |Cite
|
Sign up to set email alerts
|

P662 Efficacy and safety of tofacitinib in patients with moderate-to-severe ulcerative colitis: A real-world retrospective study

Abstract: Background Tofacitinib is an orally active, small-molecule Janus kinase inhibitor, recently approved for the treatment of moderate to severe ulcerative colitis (UC) refractory to corticosteroid. However, currently, there is inadequate evidence for efficacy of Tofacitinib in UC patients. Therefore, our objective was to evaluate the efficacy and safety of Tofacitinib for inducing and maintaining remission in UC patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…Of the 202 citations identified with the search strategy, 17 studies including 1162 patients with UC were eligible to be included in this review. [5][6][7][11][12][13][14][15][16][17][18][19][20][21][22][23][24] (Supplementary Table 1). Six studies were reported as full-text articles, and 11 were conference proceedings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 202 citations identified with the search strategy, 17 studies including 1162 patients with UC were eligible to be included in this review. [5][6][7][11][12][13][14][15][16][17][18][19][20][21][22][23][24] (Supplementary Table 1). Six studies were reported as full-text articles, and 11 were conference proceedings.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies compared response rates according to prior biologic exposure. 17,19,24 Response at week 8 was achieved in 58.1% of patients who were bio-experienced (95% CI, 49.3-66.7) versus 83% of patients who were biologic-naïve (95% CI, 56.5-99.2; Supplementary Fig. 3).…”
Section: Subgroup Analysis: Effectiveness According To Prior Biologic...mentioning
confidence: 99%
“…After excluding 32 studies for reasons documented in Figure 1, 24 articles representing 26 independent studies were included in our analysis. 7,[10][11][12][13][14][15][16][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] An RCT study design was used in 4 studies, 7,34 and the rest were observational designs. Twenty studies reported efficacy outcomes 7,[10][11][12][13][14][15][16]31,[33][34][35][36][37][38][39][40]42,44,45 and 25 studies reported safety outcomes.…”
Section: Resultsmentioning
confidence: 99%
“… 23 Real-life Japanese studies have reported week 8 clinical remission and response rates of 27.7–50.5% and 46.6–66.3%, respectively. 24 27 They have also reported that 41–43.5% and 45–47.1% of patients showed remission and response at weeks 48–52, respectively. 26 , 27 These results were also slightly numerically different from those of our study, probably because of the difference in the patients’ characteristics and the definitions of clinical outcomes.…”
Section: Discussionmentioning
confidence: 88%
“… 23 However, real-world studies on the effectiveness and safety of tofacitinib in Asian patients have still been limited to a single-center-based design and no reports from Korea are yet available. 24 28 …”
Section: Introductionmentioning
confidence: 99%